BEHIND GOD COMPLEX: SUPERMAN’S NARCISSISM IN MOVIE OF SUPERMAN: RED SON - Wijayanto, Bagus Pratama; Napitupulu, Johanes Claudio Perdana; Ramadhani, Nasywa Nuzula; Rahmadianti, Happy Julia; Pasopati, Rommel Utungga (Universitas Negeri Surabaya, 2026)
This article examines how the Superman: Red Son movie by Sam Liu portrays Superman’s narcissism behavior. The movie is about another universe in DC Comics where Superman is born in Soviet Union within Cold War. It also shows how Superman is practicing his overconfidence within his God Complex as the sole legitimate ruler for his people in Superman: Red Son. In this movie, Superman is depicted as a very tyrannical Soviet leader. Superman also thinks that he is better than other people. He believes that all that he does is justified and bearing truth according to his own values. Through qualitative method, this article would like to explore more whether Superman’s God Complex is closely related to condition of narcissism behavior. In analysis, Superman is proved to practice narcissism as a high sense of self-importance, being arrogant to other people, and always act high and mighty toward the people presence. In conclusion, it is clear that Superman’s God Complex is in matter of narcissism behavior, especially in his action towards other people.